The Development of Assessment Instruments of Critical Thinking Ability in Mathematics Learning in Elementary School - Kurnianti, Endang M.; Sarifah, Iva (International Journal of Business, Law, and Education, 2023)
The purpose of This research is to develop assessment instruments of critical thinking ability in mathematics learning in elementary school. This research using mixed methods research. The planning and preparation mechanisms for critical thinking ability assessment instruments in elementary mathematics learning in this study are adapted from the Borg and Gall models and the Dick, Carey and Carey models. Based on this model, the stages of the research: (1) Research and information gathering that includes preliminary study and needs analysis; (2) development of a draft that includes the planning and development of the initial form of the product; (3) product trials and revisions that include expert judgement, one to one evaluation, and field test; and (4) finalization and dissemination. The results showed that the assessment instruments of critical thinking ability in elementary school especially in mathematics learning have qualified aspects of materials, construction, and language. Thus, this critical thinking ability assessment instrument can be used as one of the instruments used in carrying out the assessment of mathematics learning in elementary school. The results of this study recommend that other assessment instruments be produced that can be used to assess other skills in mathematics learning in elementary school, such as creative thinking ability, systematic thinking ability, associative, evaluative, and others in order to help the pupil to fulfill their competencies.